Where is the mind within the brain? Transient selection of subnetworks by metabotropic receptors and G protein-gated ion channels. (April 2023) - Nikolić, Danko
Abstract: Perhaps the most important question posed by brain research is: How the brain gives rise to the mind. To answer this question, we have primarily relied on the connectionist paradigm: The brain's entire knowledge and thinking skills are thought to be stored in the connections; and the mental operations are executed by network computations. I propose here an alternative paradigm: Our knowledge and skills are stored in metabotropic receptors (MRs) and the G protein-gated ion channels (GPGICs). Here, mental operations are assumed to be executed by the functions of MRs and GPGICs. As GPGICs have the capacity to close or open branches of dendritic trees and axon terminals, their states transiently re-route neural activity throughout the nervous system. First, MRs detect ligands that signal the need to activate GPGICs. Next, GPGICs transiently select a subnetwork within the brain. The process of selecting this new subnetwork is what constitutes a mental operation – be it in a form of directed attention, perception or making a decision. Synaptic connections and network computations play only a secondary role, supporting MRs and GPGICs. According to this new paradigm, the mind emerges within the brain as the function of MRs and GPGICs whose primary function is to continually select the pathways over which neural activity will be allowed to pass. It is argued that MRs and GPGICs solve the scaling problem of intelligence from which the connectionism paradigm suffers. Graphical abstract: ga1 Highlights: Connectionist paradigm suffers from the scaling problem and hence, a new paradigm is needed. G protein-gated ion channels (GPGICs) close or open branches of dendritic trees and axon terminals, transiently re-routing neural activity. Metabotropic receptors (MRs) have the capacity to learn the conditions under which GPGICs need to be activated. Mental operations may solely be executed by the functions of MRs and GPGICs.